2014
DOI: 10.1186/s12883-014-0175-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of hip fractures in patients with dementia: a nationwide population-based study

Abstract: BackgroundDementia has been associated with an increased risk of hip fracture. However, little research has been conducted on the impact of dementia on wrist or vertebral fracture development. The aim of this study was to investigate whether dementia is a risk factor for different types of fracture in Taiwan.MethodsThe study sample was drawn from Taiwan’s National Health Insurance Research Database of reimbursement claims, and comprised 1408 patients who visited ambulatory care centers or were hospitalized wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
62
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 30 publications
8
62
0
2
Order By: Relevance
“…Dementia independently increases hip fracture risk 2.7‐fold . Available study outcomes on the association between dementia and risk of fractures at other sites (wrist and vertebral) are inconsistent . Because of modest effect sizes, inconsistent study results, and side effect profiles of the medications, clinical uptake of dementia medications has been limited .…”
Section: Discussionmentioning
confidence: 99%
“…Dementia independently increases hip fracture risk 2.7‐fold . Available study outcomes on the association between dementia and risk of fractures at other sites (wrist and vertebral) are inconsistent . Because of modest effect sizes, inconsistent study results, and side effect profiles of the medications, clinical uptake of dementia medications has been limited .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that up to 90% of hospitalizations in patients with dementia are related to falls (Harvey, Mitchell, Brodaty, Draper, & Close, 2015). Fractures about the hip are commonly studied, and for patients with dementia who sustain a hip fracture, dementia is independently associated with hip fractures (Wang et al, 2014). Thirty-day mortality is doubled (Khan, Hossain, Ahmed, Muthukumar, & Mohsen, 2013), and one-year mortality rates are roughly 1.5 times higher in patients with dementia than their comorbidity and age-matched peers without dementia (Maceroli, Nikkel, Mahmood, & Elfar, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with dementia are at higher risk of hip fractures 16. Major depression has been identified as a risk factor for falls; a meta-analysis of published studies identified that older adults with major depression had a fourfold increased risk for falling as compared with non-depressed older adults 17.…”
Section: Discussionmentioning
confidence: 99%